Wild mushroom extracts as inhibitors of bacterial biofilm formation - Alves, Maria José (2015)
Microorganisms can colonize a wide variety of medical devices, putting patients in risk for local and systemic infectious complications, including local-site infections, catheter-related bloodstream infections, and endocarditis. These microorganisms are able to grow adhered to almost every surface, forming architecturally complex communities termed biofilms. The use of natural products has been extremely successful in the discovery of new medicine, and mushrooms could be a source of natural antimicrobials. The present study reports the capacity of wild mushroom extracts to inhibit in vitro biofilm formation by multi-resistant bacteria. Four Gram-negative bacteria biofilm producers (Escherichia coli, Proteus mirabilis, Pseudomonas aeruginosa, and Acinetobacter baumannii) isolated from urine were used to verify the activity of Russula delica, Fistulina hepatica, Mycena rosea, Leucopaxilus giganteus, and Lepista nuda extracts. The results obtained showed that all tested mushroom extracts presented some extent of inhibition of biofilm production.Pseudomonas aeruginosa was the microorganism with the highest capacity of biofilm production, being also the most susceptible to the extracts inhibition capacity (equal or higher than 50%). Among the five tested extracts against E. coli, Leucopaxillus giganteus (47.8%) and Mycenas rosea (44.8%) presented the highest inhibition of biofilm formation. The extracts exhibiting the highest inhibitory effect upon P. mirabilis biofilm formation were Sarcodon imbricatus (45.4%) and Russula delica (53.1%). Acinetobacter baumannii was the microorganism with the lowest susceptibility to mushroom extracts inhibitory effect on biofilm production (highest inhibition—almost 29%, by Russula delica extract). This is a pioneer study since, as far as we know, there are no reports on the inhibition of biofilm production by the studied mushroom extracts and in particular against multi-resistant clinical isolates; nevertheless, other studies are required to elucidate the mechanism of action.